21 Inappropriate hospitalisations, aggressive treatments, and insufficient deprescribing: the medicalisation of death from natural causes. (4th December 2019) - Cardona, Magnolia; Lewis, Ebony; Stehlik, Paulina; Sun, Shelley; Clark, Justin
Abstract : Objectives: To generate evidence for extent of and determinants of overtreatment of older people (60+ years) in hospitals and identify possible solutions. Methods: We conducted four systematic reviews on the following topics: Definitions and magnitude of non-beneficial treatments in the last six months of life. Type and extent of inappropriate hospitalisations near the end of life. Effectiveness of advance care documentation to prevent non-beneficial treatments. Effectiveness of hospital-based interventions for deprescribing older dying people on polypharmacy. Results: 391 studies identified, of which 38 high quality studies in 10 countries were included. Pooled estimates indicate widespread practice of low-value care in hospitals (from imaging to resuscitation). The mean rate of low-value ICU admission was 10% (95% CI 0–33%). The corresponding pooled figure for chemotherapy in the last 6 weeks of life was 33% (95% CI 24–41%). 571 articles identified on inappropriate hospitalisation, of which 16 high-quality non-RCTs in eight countries were included, but heterogeneity of outcomes precluded meta-analysis. Results indicated wide variation (from 1.7% to 67.0%) on the extent of clinically inappropriate decision to admit for ambulatory-sensitive conditions, family-driven admissions due to poor availability of community services (up to 10.5%), or too late to benefit (up to 35%). 2, 621 unique studies identified and 24 qualitative or mixed methods studies included from 10 countries. They reported high level of clinician and patient perceived effectiveness of advance care documentation in triggering timely end-of-life discussions. However, no quantifiable data could demonstrate actual effectiveness. Search results for effectiveness of interventions to deprescribe older patients returned 568 studies but almost none targeted deprescribing of older people deemed to be in the last year or months of life. Further, the vast majority of published evaluations were low-level evidence designs (non-RCTs or uncontrolled studies). High-quality research is needed on effective strategies to contain overprescribing near the end of life. Conclusions: The medicalization of death as a by-product of medical technological advances has led to widespread low-value care practices and unsustainable healthcare costs associated with inappropriate hospitalisations and aggressive management. Major determinants were prognostic uncertainty, lack of competence in recognition of dying, poor communication with patients, disagreement within specialist teams, and family pressure. Strategies to minimise the extent of overtreatment of older patients across hospitals may include training of health professionals in confidently identifying risk of death; resource redistribution to enable referrals to non-acute hospital care pathways; multifaceted interventions to reduce unnecessary intensive inpatient monitoring and overtreatment; public awareness campaigns to improve advance care planning and reduce social expectation of immortality; and health policies to reimburse doctors, nurses and allied health for conducting comprehensive assessments and value-driven end-of-life discussions with older patients. We need to re-embrace the concept of death from old age and irreversible chronic illness as a normal part of the life cycle. While a certain level of non-beneficial treatment is inevitable and sometimes justifiable on compassionate grounds, efforts to prevent or minimise avoidable low-value care are warranted to prevent a collapse of the healthcare system.